2012
DOI: 10.1080/10286020.2012.656605
|View full text |Cite
|
Sign up to set email alerts
|

Effects of capsaicin and dihydrocapsaicin on human and rat liver microsomal CYP450 enzyme activitiesin vitroandin vivo

Abstract: Capsaicin and dihydrocapsaicin, the two most abundant members of capsaicinoids in chili peppers, are widely used as food additives and for other purposes. In this study, we examined the inhibitory potentials of capsaicin and dihydrocapsaicin against CYP1A2, CYP2C9, CYP2C19, CYP2D6, CYP2E1, and CYP3A4/5 activities in human liver microsomes. The effects of these two capsaicinoids on CYP450 enzymes were also evaluated in vivo in rats. The results demonstrated that capsaicin and dihydrocapsaicin moderately inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…It is unknown whether there is interaction between capsaicin and DPP-4 inhibitors. Several studies show that capsaicin, but not DPP-4 inhibitors (except saxagliptin), can inhibit cytochrome P450 (CYP 3A4/A5) enzymes (4850). Thus, in general, interactions between DPP-4 inhibitors and capsaicin are absent or minor.…”
Section: Discussionmentioning
confidence: 99%
“…It is unknown whether there is interaction between capsaicin and DPP-4 inhibitors. Several studies show that capsaicin, but not DPP-4 inhibitors (except saxagliptin), can inhibit cytochrome P450 (CYP 3A4/A5) enzymes (4850). Thus, in general, interactions between DPP-4 inhibitors and capsaicin are absent or minor.…”
Section: Discussionmentioning
confidence: 99%
“…Capsaicin is mainly metabolized in the liver through cytochrome P450-dependent reactions and peroxydase enzymes, producing three major metabolites, 16-hydroxycapsaicin, 17-hydroxycapsaicin, and 16, 17-hydroxycapsaicin, and is scarcely excreted in the urine (Suresh and Srinivasan 2010). Although many enzymes may play some role in hepatic drug metabolism, cytochrome P450 enzymes are quantitatively the most important, and it has been proposed that many drug-drug interactions result from the alteration (increase or decrease) in the activities of these enzymes (Zhang et al 2012;Zhai et al 2013). However, Babbar et al demonstrated that at concentrations occurring after ingestion of chili peppers or topical administration of a high-concentration patch, capsaicin did not cause direct inhibition of any CYP enzyme (Babbar et al 2010).…”
mentioning
confidence: 98%
“…The cytochrome P450 family includes many isoenzymes, such as CYP1A2, CYP2C9, CYP2C19, CYP2D6, and CYP3A4, which metabolize over 90% of clinical drugs, and the functions of enzymes of the same family are similar [2][3][4]. Assessing drug-drug interactions (DDIs), especially the evaluation of the effect of a new drug on the CYP450 enzyme activities, is essential and important to understanding toxic and inhibitory effects [5].…”
Section: Introductionmentioning
confidence: 99%